Analisis Teori Antrian dalam Pelaksanaan Vaksinasi Covid-19 di Puskesmas Tapen - Rafiantika Megahnia Prihandini; Hilwa Ainur Rizki; Susi Setiawani (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2023)
This study was motivated by the Covid-19 pandemic in Indonesia. As a response to the pandemic, the government provided widespread vaccination services for the public. However, the large-scale implementation of the vaccination program led to uncontrolled patient arrivals due to crowding at vaccination sites. This situation contributed to the potential spread of new clusters of the coronavirus. The research applies queuing theory to analyze several key aspects: the average number of patient arrivals, the average quality of service, and the optimization of the number of healthcare workers needed at the Tapen Health Center. The study focuses specifically on analyzing the queuing system and patient waiting times during the vaccination process. Data were collected through interviews and direct observation of the healthcare personnel involved in the Covid-19 vaccination service. The results indicate that the queuing system implemented at the Tapen Health Center has provided optimal service performance, with the capacity to serve an average of 7 to 17 people between 08:00 and 11:00 AM.